Competitive Economic Development of The Republic of Moldova - Perchinschi Natalia; Gribincea Alexandr (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2018)
With this general framework in mind, this section has explained through various examples the circumstances in which economic theory would justify a temporary increase in trade barriers – even above the level of commitments in a trade agreement. These circumstances include when an import surge provides an argument for an increase in trade barriers as well as when a change in demand or supply or in policy leads to a sharp contraction for a particular sector and this, in turn, has a negative externality (like in the case of the one-company town). Another argument for trade policy intervention is when something alters the degree of competition in the market – for example, if a company indulges in predatory dumping. Other circumstances include developing countries providing support to infant industry, action to address balance of payment crises, and responding to a sharp increase in the world price of a product. In all these cases, the adoption of restrictive trade policy can be justified as a second-best option.